Hydrogen fuel cell cooling liquid and preparation method thereof
By using a hydrogen fuel cell coolant composed of multiple compounds, the problems of flammability, environmental pollution and evaporation losses of alcohol coolants are solved, and high safety, low conductivity and excellent thermal conductivity are achieved, which extends the The service life of fuel cells.
Patent Information
- Application Number
- CN202510057730.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-02-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The alcohol coolant in existing hydrogen fuel cells is flammable, harmful to the environment, and the high vapor pressure leads to evaporation losses, affecting the normal operation of the fuel cells.
Provided is a hydrogen fuel cell coolant, which is modified from water, carbon nano-modified propylene glycol ether, 1-butyl-3-methylimidazole tetrafluoroborate, polyethylene glycol, organic borate esters, polyacrylic acid, quaternary The ammonium salt and silver nanoparticles are composed of and prepared by specific mixing and treatment methods. They have various functions such as low conductivity, anti-freeze, cooling, anti-corrosion, anti-scaling, anti-bacterial and other functions.
The coolant is non-flammable, improves the safety of the hydrogen fuel cell system, enhances heat conduction, improves heat dissipation efficiency, reduces evaporation losses, extends service life, and has good material compatibility, reducing corrosion and pollution problems .
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of hydrogen fuel cells, and in particular to a hydrogen fuel cell coolant and a preparation method thereof. Background Art
[0002] As the global energy crisis and environmental pollution become increasingly serious, the development and utilization of clean energy has become a common focus of attention for countries around the world. As an efficient and clean energy conversion device, hydrogen fuel cells have attracted much attention due to their zero emissions and high energy density. However, in actual application, the performance and life of hydrogen fuel cells are affected by many factors, among which the choice of coolant is particularly critical.
[0003] Traditional alcohol coolants, such as methanol and ethanol, have long been widely used in hydrogen fuel cells due to their good thermal conductivity and compatibility with fuel cell materials. This type of coolant can effectively take away the heat generated by the fuel cell, ensuring that the battery operates at a suitable temperature, thereby maintaining its stability and efficiency. However, there are also some problems with alcohol coolants that cannot be ignored. First, they are flammable substances. Once they leak or encounter a fire source, they are very likely to cause safety accidents and bring potential dangers to users. Secondly, alcohol coolants are harmful to the environment. Long-term use will cause pollution to water and soil, which is not conducive to the protection of the ecological environment. In addition, the vapor pressure of alcohol coolants is high, which can easily lead to evaporation losses of coolants, which not only increases maintenance costs, but may also affect the normal operation of fuel cells.
[0004] Based on this, it is of great significance to provide a non-alcohol hydrogen fuel cell coolant that is environmentally friendly, highly safe, has good thermal conductivity, good thermal stability and good material compatibility. Summary of the invention
[0005] The purpose of the present invention is to provide a hydrogen fuel cell coolant which has multiple functions such as antifreeze, cooling, corrosion prevention, scale prevention, and antibacterial, and has the characteristics of low conductivity and high membrane electrode compatibility.
[0006] In order to achieve the above object, the first aspect of the present invention provides a hydrogen fuel cell coolant, which is composed of the following substances in parts by weight: 60-90 parts by weight of water, 5-20 parts by weight of carbon nano-modified propylene glycol ether, 0.5-5 parts by weight of 1-butyl-3-methylimidazole tetrafluoroborate, 3-12 parts by weight of polyethylene glycol, 0.5-5 parts by weight of organic borate, 0.1-3 parts by weight of polyacrylic acid, 0.1-0.8 parts by weight of quaternary ammonium salt, and 0.01-0.4 parts by weight of silver nanoparticles; The average volume diameter of the silver nanoparticles is 20-100 nm.
[0007] The second aspect of the present invention provides a method for preparing a hydrogen fuel cell coolant, the method using the substance in the hydrogen fuel cell coolant of the first aspect, the method comprising: (1) mixing water and carbon nano-modified propylene glycol ether for a first contact to obtain a premixed solution I; (2) mixing the premixed solution I with 1-butyl-3-methylimidazolium tetrafluoroborate for a second contact to obtain a premixed solution II; (3) mixing polyethylene glycol, polyacrylic acid, and organic borate with the premixed solution II for a third contact to obtain a premixed solution III; (4) under ultrasonic conditions, the premixed solution III is mixed with the quaternary ammonium salt and the silver nanoparticles for a fourth contact, the pH is adjusted and then the impurities are removed by an ultrafine filtration device, and then the hydrogen fuel cell coolant is obtained after ion exchange; The dosage of each substance is: 60-90 parts by weight of water, 5-20 parts by weight of carbon nano-modified propylene glycol ether, 0.5-5 parts by weight of 1-butyl-3-methylimidazole tetrafluoroborate, 3-12 parts by weight of polyethylene glycol, 0.5-5 parts by weight of organic borate, 0.1-3 parts by weight of polyacrylic acid, 0.1-0.8 parts by weight of quaternary ammonium salt, and 0.01-0.4 parts by weight of silver nanoparticles.
[0008] The third aspect of the present invention provides a hydrogen fuel cell coolant prepared by the method described in the second aspect.
[0009] Compared with the prior art, the method provided by the present invention has at least the following beneficial effects: (1) The hydrogen fuel cell coolant provided by the present invention has low electrical conductivity and is non-flammable, thereby improving the overall safety of the hydrogen fuel cell system. In addition, while optimizing the anti-corrosion and antibacterial properties, the coolant also enhances the heat conduction capacity, effectively improving the heat dissipation efficiency of the hydrogen fuel cell system and ensuring the stability and life of the battery under high-temperature working conditions. The coolant evaporation loss is reduced, the maintenance frequency and cost of the cooling system are reduced, and the service life of the coolant is increased. The coolant has good compatibility with other materials in the hydrogen fuel cell system, reduces corrosion and pollution problems, and maintains the performance of the battery. (2) In the method provided by the present invention, polyethylene glycol, polyacrylic acid, and organic borate can produce a synergistic effect, and the quaternary ammonium salt added later can interact with these polymer material systems, thereby increasing the surface activity, stability, temperature resistance, and conductivity of the system; (3) In the method provided by the present invention, the silver nanoparticles can interact with the cationic part of the quaternary ammonium salt, so that the surface properties of the silver nanoparticles change, forming a stable nanocomposite and changing the release rate of silver ions, thereby effectively inhibiting bacteria and molds and enhancing the antibacterial property and stability of the system. DETAILED DESCRIPTION
[0010] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0011] As mentioned above, the first aspect of the present invention provides a hydrogen fuel cell coolant, which is composed of the following substances in parts by weight: 60-90 parts by weight of water, 5-20 parts by weight of carbon nano-modified propylene glycol ether, 0.5-5 parts by weight of 1-butyl-3-methylimidazole tetrafluoroborate, 3-12 parts by weight of polyethylene glycol, 0.5-5 parts by weight of organic borate, 0.1-3 parts by weight of polyacrylic acid, 0.1-0.8 parts by weight of quaternary ammonium salt, and 0.01-0.4 parts by weight of silver nanoparticles; The average volume diameter of the silver nanoparticles is 20-100 nm.
[0012] Preferably, the weight ratio of the carbon nano-modified propylene glycol ether to the 1-butyl-3-methylimidazolium tetrafluoroborate is 4-9: 1. In this preferred embodiment, the thermal conductivity and electrochemical stability of the coolant can be significantly improved.
[0013] Preferably, the weight ratio of the quaternary ammonium salt to the silver nanoparticles is 2-8: 1. In this preferred embodiment, the antibacterial and anti-corrosion properties of the coolant can be effectively enhanced.
[0014] Further preferably, the carbon nano-modified propylene glycol ether is a product prepared by a method comprising the following steps: The pretreated carbon nanoparticles are contacted and mixed with propylene glycol ether, and then subjected to ultrasonic treatment to obtain the carbon nano-modified propylene glycol ether. This preferred case is conducive to improving the thermal management performance of the coolant.
[0015] More preferably, the weight ratio of the pretreated carbon nanoparticles to the propylene glycol ether is 10-20:100.
[0016] More preferably, the ultrasonic treatment is carried out under stirring conditions and at least meets the following conditions: a rotation speed of 400-600 rpm, a power of 300-500 W, and a time of 10-20 min.
[0017] Preferably, the pretreated carbon nanoparticles are products prepared by a method comprising the following steps: S1, soaking the carbon nanoparticles in an acid washing solution for 1-3 hours to obtain a mixture I; S2, heating the mixture I to 100-120° C. and reflux for 2-5 h, and washing with deionized water to obtain a mixture II; S3, reacting the mixture II with the titanate coupling agent solution, and then calcining the mixture in an inert gas at 800-900° C. for 1-2 hours to obtain the pretreated carbon nanoparticles. In this preferred embodiment, the heat conduction performance of the coolant can be further enhanced and the service life of the coolant can be extended.
[0018] Preferably, in step S1, the pickling solution is a mixture of concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:1.
[0019] Preferably, in step S3, the titanate coupling agent solution is an ethanol solution of a titanate coupling agent, and the concentration is 0.5-2.0 wt %.
[0020] It should be noted that, in the present invention, the water is deionized water and / or distilled water.
[0021] As mentioned above, the second aspect of the present invention provides a method for preparing a hydrogen fuel cell coolant, the method using the substance in the hydrogen fuel cell coolant of the first aspect, the method comprising: (1) mixing water and carbon nano-modified propylene glycol ether for a first contact to obtain a premixed solution I; (2) mixing the premixed solution I with 1-butyl-3-methylimidazolium tetrafluoroborate for a second contact to obtain a premixed solution II; (3) mixing polyethylene glycol, polyacrylic acid, and organic borate with the premixed solution II for a third contact to obtain a premixed solution III; (4) under ultrasonic conditions, the premixed solution III is mixed with the quaternary ammonium salt and the silver nanoparticles for a fourth contact, the pH is adjusted and then the impurities are removed by an ultrafine filtration device, and then the hydrogen fuel cell coolant is obtained after ion exchange; The dosage of each substance is: 60-90 parts by weight of water, 5-20 parts by weight of carbon nano-modified propylene glycol ether, 0.5-5 parts by weight of 1-butyl-3-methylimidazole tetrafluoroborate, 3-12 parts by weight of polyethylene glycol, 0.5-5 parts by weight of organic borate, 0.1-3 parts by weight of polyacrylic acid, 0.1-0.8 parts by weight of quaternary ammonium salt, and 0.01-0.4 parts by weight of silver nanoparticles.
[0022] It should be noted that the present invention has no special requirements for the ultrafiltration device and the ion exchange resin, and conventional technical means in the art can be used. For example, the filtration accuracy of the ultrafiltration device is 1 μm, and the ion exchange can be carried out using Rohm and Haas AMBERJET UP6040 ion exchange resin.
[0023] Preferably, the method of the present invention is carried out at 20-50°C.
[0024] Preferably, the temperatures of the second contacting and the third contacting are each independently 28-50°C.
[0025] Preferably, the temperature of the fourth contacting is 20-35°C.
[0026] According to a preferred embodiment, in step (2), the first contact, the second contact, the third contact and the fourth contact are all carried out under stirring conditions, and each independently at least satisfies: a rotation speed of 400-600 rpm and a time of 20-50 min.
[0027] Preferably, in step (4), the power of the ultrasonic condition is 400-500W.
[0028] Preferably, in step (4), the pH is adjusted using a boric acid buffer solution or a phosphate buffer solution, and the adjusted pH is 7.5-8.5.
[0029] As mentioned above, the third aspect of the present invention provides a hydrogen fuel cell coolant prepared by the method described in the second aspect.
[0030] The present invention is described in detail below by way of examples. Unless otherwise specified, the raw materials used are all common commercially available products.
[0031] Unless otherwise specified, each “part by weight” in the present invention means 10 g.
[0032] Silver nanoparticles: The average volume diameter is 60nm.
[0033] Preparation Example A-1: Preparation of pretreated carbon nanoparticles: S1, soaking the carbon nanoparticles in an acid washing solution (a mixture of concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:1) for 1.5 hours to obtain a mixture I; S2, heating the mixture I to 100° C. and refluxing for 3 h, washing with deionized water until neutral to obtain a mixture II; S3, subjecting the mixture II to a first reaction with an ethanol solution of the titanate coupling agent (with a concentration of 1.0 wt%), and then calcining the mixture under an inert gas at 800° C. for 2 h to obtain pretreated carbon nanoparticles, named a1.
[0034] Preparation Example B-1: 10.5 g of pretreated carbon nanoparticles (a1) were added to propylene glycol ether at a weight ratio of 15:100 for contact mixing, and then ultrasonically treated under stirring conditions (speed of 500 rpm, power of 300 W, time of 15 min) to obtain the carbon nano-modified propylene glycol ether, named b1.
[0035] Preparation Example B-2: 10.5 g of pretreated carbon nanoparticles (a1) were added to propylene glycol ether at a weight ratio of 25:100 for contact mixing, and then ultrasonically treated under stirring conditions (speed of 500 rpm, power of 300 W, time of 15 min) to obtain the carbon nano-modified propylene glycol ether, named b2.
[0036] Preparation Example B-3: The unpretreated carbon nanoparticles (10.5 g) in Preparation Example A-1 were directly added to propylene glycol ether at a weight ratio of 15:100 for contact mixing, and then ultrasonically treated under stirring conditions (speed of 500 rpm, power of 300 W, time of 15 min) to obtain the carbon nano-modified propylene glycol ether, named b3.
[0037] Preparation Example C-1: This preparation example is used to illustrate that the hydrogen fuel cell coolant provided by the present invention is prepared according to the following steps: (1) adding carbon nano-modified propylene glycol ether (b1) into water at 20° C. and stirring at a rotation speed of 400 rpm for 25 minutes to perform a first contact, thereby obtaining a premixed solution I; (2) mixing the premixed solution I with 1-butyl-3-methylimidazolium tetrafluoroborate at 28° C. and 400 rpm for 25 minutes for a second contact to obtain a premixed solution II; (3) mixing polyethylene glycol, polyacrylic acid, and organic borate with the premixed solution II at 28° C. and 400 rpm for 50 min to perform a third contact, thereby obtaining a premixed solution III; (4) at 20° C. and under ultrasonic conditions (power 500 W), the premixed solution III was mixed with the quaternary ammonium salt and the silver nanoparticles (silver nanoparticles I) at a speed of 400 rpm for 30 minutes to perform a fourth contact, the pH value was adjusted to 7.5 with a phosphate buffer solution, and then impurities were removed by an ultrafine filtration device (filtration accuracy of 1 μm), and then ion exchange (using Rohm and Haas AMBERJET UP6040 ion exchange resin) was performed to obtain a hydrogen fuel cell coolant, which was named P1; Among them, the amount of each substance used is: 82 parts by weight of water, 8 parts by weight of carbon nano-modified propylene glycol ether, 2 parts by weight of 1-butyl-3-methylimidazole tetrafluoroborate, 4 parts by weight of polyethylene glycol, 2 parts by weight of organic borate, 1.5 parts by weight of polyacrylic acid, 0.4 parts by weight of quaternary ammonium salt, and 0.1 parts by weight of silver nanoparticles.
[0038] Preparation Example C-2: This preparation example was carried out in a similar manner to that of Preparation Example C-1, except that the amounts of carbon nano-modified propylene glycol ether and 1-butyl-3-methylimidazolium tetrafluoroborate were 5 parts by weight and 5 parts by weight, respectively; The final product is a hydrogen fuel cell coolant named P2.
[0039] Preparation Example C-3: This preparation example is carried out in a similar manner to that of Preparation Example C-1, except that in step (1), the carbon nano-modified propylene glycol ether used is b2; The final product is a hydrogen fuel cell coolant named P3.
[0040] Preparation Example C-4: This preparation example is carried out in a similar manner to that of Preparation Example C-1, except that in step (1), the carbon nano-modified propylene glycol ether used is b3; The final product is a hydrogen fuel cell coolant named P4.
[0041] Comparative Example 1: This comparative example was carried out using a method similar to that of Preparation Example C-1, except that in step (1), an equal mass of propylene glycol ether was used instead of carbon nano-modified propylene glycol ether for the first contact; The final product is a hydrogen fuel cell coolant named DP1.
[0042] Comparative Example 2: This comparative example was prepared by a method similar to that of Preparation Example C-1, except that in step (4), the amount of the quaternary ammonium salt was 0 parts by weight, and the amount of the silver nanoparticles was 0.5 parts by weight; The final product is a hydrogen fuel cell coolant named DP2.
[0043] Test Example 1: The hydrogen fuel cell coolant prepared in the above example was subjected to the following performance tests, including: Antifreeze performance: tested in accordance with standard "SH / T 0090"; Conductivity: Use a conductivity meter to test according to the standard "GB / T11446.4 Test method for resistivity of electronic grade water"; Measure thermal conductivity: thermal conductivity at 60°C; Ion suppression performance: The test is carried out in accordance with the aluminum, steel, and brass metal test pieces and the metal test piece cleaning method specified in "SH / T 0085". The metal test piece is immersed in the solution, but no galvanic pair is formed. The test temperature is raised to 150°C, and the test cycle is 168h. The metal corrosion of the test sample reflects the metal ion suppression ability; Proton membrane compatibility: According to the proton conductivity test in the standard "GB / T 20042.3", before the test, the proton membrane is immersed in a coolant at 80℃±2℃ for 1 hour, and then the proton conductivity is measured. If it drops by more than 5% of the original value, it is unqualified, and if it drops by ≤5% of the original value, it is qualified.
[0044] Stability test: The hydrogen fuel cell coolant is sealed and stored at 55°C for 15 days, and the time when turbidity appears is recorded in days. If no turbidity appears after 15 days of storage, it is recorded as "none".
[0045] Antibacterial test: Take the circulating tap water used in the factory workshop for 2 weeks as the blank water sample, dilute it with the coolant in a 1:1 ratio, and culture it at 35℃ for 48 hours. Refer to the standard "SY / T5329-1994" and use the extinction dilution and three-repetition method to detect the antibacterial rate of saprophytes, sulfate-reducing bacteria and iron wire bacteria on the 7th day, and then take the average of the three to record the result.
[0046] The specific test results are shown in Table 1; ; It can be seen from the above results that the hydrogen fuel cell coolant provided by the present invention not only has excellent antifreeze performance, can maintain fluidity in extremely low temperature environments, and prevent the fuel cell system from being damaged by icing, but also has efficient cooling capabilities, can quickly absorb and conduct a large amount of heat generated by the fuel cell during operation, and ensure the stability of the battery operating temperature. In addition, the coolant also has excellent anti-corrosion properties and antibacterial properties, and can effectively resist corrosion of metal parts. More importantly, the coolant of the present invention has low electrical conductivity, which significantly reduces the risk of electrolyte leakage or electrochemical corrosion. In addition, the coolant is also optimized for compatibility with the membrane electrode material of the fuel cell to ensure that while dissipating heat efficiently, it will not adversely affect the performance and life of the membrane electrode, thereby achieving high membrane electrode compatibility.
[0047] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A hydrogen fuel cell coolant, characterized in that: The hydrogen fuel cell coolant is composed of the following materials in parts by weight: 60-90 parts by weight of water, 5-20 parts by weight of carbon nano-modified propylene glycol ether, 0.5-5 parts by weight of 1-butyl-3-methylimidazole tetrafluoroborate, 3-12 parts by weight of polyethylene glycol, 0.5-5 parts by weight of organic borate, 0.1-3 parts by weight of polyacrylic acid, 0.1-0.8 parts by weight of quaternary ammonium salt, and 0.01-0.4 parts by weight of silver nanoparticles; The average volume diameter of the silver nanoparticles is 20-80 nm; The carbon nano-modified propylene glycol ether is a product prepared by a method comprising the following steps: The pretreated carbon nanoparticles are contacted and mixed with propylene glycol ether, and then subjected to ultrasonic treatment to obtain the carbon nano-modified propylene glycol ether; The pretreated carbon nanoparticles are products prepared by a method comprising the following steps: S1, soaking the carbon nanoparticles in an acid washing solution for 1-3 hours to obtain a mixture I; S2, heating the mixture I to 100-120° C. and reflux for 2-5 h, and washing with deionized water to obtain a mixture II; S3, subjecting the mixture II to a first reaction with a titanate coupling agent solution, and then calcining the mixture in an inert gas at 800-900° C. for 1-2 h to obtain the pretreated carbon nanoparticles.
2. The hydrogen fuel cell coolant according to claim 1, wherein: The weight ratio of the carbon nano-modified propylene glycol ether to the 1-butyl-3-methylimidazole tetrafluoroborate is 4-9:
1.
3. The hydrogen fuel cell coolant according to claim 1 or 2, wherein: The weight ratio of the quaternary ammonium salt to the silver nanoparticles is 2-8:
1.
4. The hydrogen fuel cell coolant according to claim 3, wherein: In step S1, the pickling solution is a mixture of concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:
1.
5. A method for preparing a hydrogen fuel cell coolant, the method using the substance in the hydrogen fuel cell coolant according to any one of claims 1 to 4, characterized in that: The method includes: (1) mixing water and carbon nano-modified propylene glycol ether for a first contact to obtain a premixed solution I; (2) mixing the premixed solution I with 1-butyl-3-methylimidazolium tetrafluoroborate for a second contact to obtain a premixed solution II; (3) mixing polyethylene glycol, polyacrylic acid, and organic borate with the premixed solution II for a third contact to obtain a premixed solution III; (4) under ultrasonic conditions, the premixed solution III is mixed with the quaternary ammonium salt and the silver nanoparticles for a fourth contact, the pH is adjusted and then the impurities are removed by an ultrafine filtration device, and then the hydrogen fuel cell coolant is obtained after ion exchange; The dosage of each substance is: 60-90 parts by weight of water, 5-20 parts by weight of carbon nano-modified propylene glycol ether, 0.5-5 parts by weight of 1-butyl-3-methylimidazole tetrafluoroborate, 3-12 parts by weight of polyethylene glycol, 0.5-5 parts by weight of organic borate, 0.1-3 parts by weight of polyacrylic acid, 0.1-0.8 parts by weight of quaternary ammonium salt, and 0.01-0.4 parts by weight of silver nanoparticles.
6. The method according to claim 5, wherein: In step (2), the first contact, the second contact, the third contact and the fourth contact are all carried out under stirring conditions, and each independently satisfies at least: a rotation speed of 400-600 rpm and a time of 20-50 min.
Citation Information
Patent Citations
Hydrogen fuel cell cooling liquid with high heat transfer coefficient and preparation method thereof
CN116004193A
Battery cooling liquid and preparation method thereof
CN117050733A
Composition for battery cooling liquid, battery cooling liquid and preparation method of battery cooling liquid
CN118496820A
Novel coolant with low electrical conductivity
US20240309257A1
Coolant composition for fuel cell
US20240417614A1